RUSSIAN RESEARCHERS OF THE SECOND PART OF THE 1960 – EARLY 1980-S ON THE HISTORY OF INTERNATIONAL COOPERATION IN THE NORTH CAUCASUS - N. I. Gasanova (Гуманитарные и юридические исследования)
This article examines the historiography of the USSR international relations on a regional level. For the analysis the author selected a range of works representing interdisciplinary approaches to the problem. The article examines the works by both historians and economists, which allows to determine the extend to which the problem was studied in the Soviet historiography. This article reveals the gaps in the scientific historical knowledge of the Soviet period, and identify ways to study the problem in the context of intellectual history.